ANALISIS KEBUTUHAN PEGAWAI PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBERDAYA MANUSIA (BKPSDM) KABUPATEN INDRAGIRI HILIR - jurnalmap map (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2022)
This study aims to analyze the needs of employees at the Human Resources Development and Human Resources Agency Indragiri Hilir Regency. This research uses descriptive qualitative research type. The focus of his research is based on job analysis and workload analysis. From the results of research conducted showed that the needs of employees at the Human Resources Development and Human Resources Development Agency Indragiri Hilir Regency have been met. This is based on the job analysis and workload analysis, where the level of competency suitability to the apparatus position is in accordance with the requirements in the job analysis, in addition to the workload and number of employees at the Human Resources Development and Human Resources Agency Indragiri Hilir Regency it is quite balanced, and for the time being there is no need for additional employees.